2008
DOI: 10.1093/annonc/mdn059
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between retroperitoneal lymphadenectomy and survival benefit in ovarian clear cell carcinoma patients?

Abstract: Our data suggest that patients with pTI-IIb CCC who underwent lymphadenectomy did not show a significant improvement in survival. There was no significant difference in the overall and disease-free survival rates in pTI-IIb CCC patients regardless of the completion of surgical staging lymphadenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 12 publications
0
50
0
Order By: Relevance
“…Saygili et al (15): had no conflict of interest statement; without long enough follow-up time; high rate of defaulters. The remaining 11 observational studies whose scores ranged from 7 to 9 with a median score of 8 (16)(17)(18)(19)(20)(23)(24)(25)(27)(28)(29) and three RCTs (21-22,26) with scores from 4 to 5 were finally included in our analyses. Figure 1 shows an overview of the process of selection.…”
Section: Literature Search and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Saygili et al (15): had no conflict of interest statement; without long enough follow-up time; high rate of defaulters. The remaining 11 observational studies whose scores ranged from 7 to 9 with a median score of 8 (16)(17)(18)(19)(20)(23)(24)(25)(27)(28)(29) and three RCTs (21-22,26) with scores from 4 to 5 were finally included in our analyses. Figure 1 shows an overview of the process of selection.…”
Section: Literature Search and Quality Assessmentmentioning
confidence: 99%
“…These articles, including 1783 cases and 1705 controls, were published between 1994 and 2013 and consisted of 11 observational studies (16)(17)(18)(19)(20)(23)(24)(25)(27)(28)(29) and three RCTs (21)(22)26). Among the included studies, SL was defined as follows: (i) either pelvic or paraaortic lymphadenectomy or both (16)(17)(19)(20)21,(23)(24)(25)(26)(27)(28)(29); (ii) >20 resected pelvic and para-aortic lymph nodes (18,22). On the other hand, USL was defined as follows: not performed or no lymphadenectomy other than suspicious lymph nodes and the removal number was <20.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A total of 1809 articles were identified in the updated search for the most appropriate surgical procedure, of which sixteen met the inclusion criteria [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the results of a large-scale non-randomized epidemiological survey (n=6,686), Chan et al [17] suggested that lymphadenectomy for stage I disease improved survival in non-clear-cell EOC patients but not in OCCC patients. In a retrospective study (n=205), Suzuki et al [18] concluded that patients with early-stage OCCC who underwent lymphadenectomy did not show a significant improvement in survival. Therefore, the therapeutic value of retroperitoneal lymphadenectomy in patients with earlystage OCCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%